Is asiaticoside effective against pain? - Mohammad, Rasyidah Ryta Ayumi; Shaik Mohamed Mossadeq, Wan Mastura; Zakaria, Zainul Amiruddin; Bakhtiar, M. Taher (Universiti Kebangsaan Malaysia, 2018)
Centella asiatica or locally known as “Pegaga” is a well-known herb that has been used in folklore medicine for centuries to treat skin problem, asthma, sstomach disorder and to improve memory. Moreover, Centella asiatica extracts exhibited significant antinocicetive activities at the central and peripheral levels. This , this research aimed to evaluate the antinociceptive activities of asiaticoside, the main bioactive constituent of Centella asiatica. We evaluated the effect of asiaticoside (1,3,5 and 10 mg/kg, orally) on the acetic acid induced abdominal constriction test and the hot plate test in mice. Our data showed that the highest dose of asiticoside (10 mg/kg) significantly (p<0.05) inhibited the abdiomial constrictions by 58.3%. Moreover, asiaticoside prolongied the latency (sec) spent by each mouse on he hot plate surface. In conclusion, asiaticoside induces analgesia at the central and peripheral levels. Further studies are required to elucidate its mechanism(s) of action.